Grading Student Behavior - Florian Schoner; Lukas Mergele; Larissa Zierow (Center for Economic Studies and ifo Institute (CESifo), 2021)
Numerous countries require teachers to assign comportment grades rating students' social and work behavior in the classroom. However, the impact of such policies on student outcomes remains unknown. We exploit the staggered introduction of comportment grading across German federal states to estimate its causal effect on students' school-to-work transitions as well as academic achievement and non-cognitive abilities. Analyzing census data, household surveys, and nationwide student assessments, we show that comportment grading does not meaningfully affect these outcomes and rule out large effect sizes. Exploring reasons for this finding, supplementary analyses suggest that comportment grades do not convey much information beyond students' grade point average.
Keywords: D91; I21; I28; J24; 330; school reforms; report cards; school-to-work transition; student achievement